Stef Soto, taco queen - Torres, Jennifer, 1980- (Little, Brown and Company, 2017)
"Seventh grader Estefania "Stef" Soto is itching to shake off the onion-and-cilantro embrace of Tia Perla, her family's taco truck. She wants nothing more than for her dad to get a normal job and for Tia Perla to be put out to pasture. It's no fun being known as the "Taco Queen" at school. But just when it looks like Stef is going to get exactly what she wants, and her family's livelihood is threatened, she will have to become the truck's unlikely champion. In this fun and multicultural middle grade novel, Stef will discover what matters the most, and ultimately embrace an identity that even includes old Tia Perla."--Publisher's website.